2010
DOI: 10.3346/jkms.2010.25.8.1237
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Congenital Central Hypoventilation Syndrome with PHOX2B Gene Mutation in a Korean Neonate

Abstract: Congenital central hypoventilation syndrome (CCHS) is a life-threatening disorder with apnea and cyanosis during sleep requiring immediate endotracheal intubation during the first day of life. The PHOX2B gene has been identified as the major gene involved in CCHS. This is the first report of a Korean neonate with CCHS confirmed to have a PHOX2B mutation with expanded alleles containing 20 polyalanine repeats that is a relatively small number compared to previous cases. The patient required intermittent ventila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Long-term prognosis is variable, with mortality rates ranging from 10% to 40% 17) . 20) . After this, two more genetically confirmed CCHS cases have been reported, both of which were accompanied by HD; these cases were finally diagnosed as Haddad syndrome 8,9) .…”
Section: Results Of Genetic Analysis Of the Phox2b Genementioning
confidence: 99%
“…Long-term prognosis is variable, with mortality rates ranging from 10% to 40% 17) . 20) . After this, two more genetically confirmed CCHS cases have been reported, both of which were accompanied by HD; these cases were finally diagnosed as Haddad syndrome 8,9) .…”
Section: Results Of Genetic Analysis Of the Phox2b Genementioning
confidence: 99%
“…2). In Korea, there are few reports describing CCHS and Haddad syndrome [11,[17][18][19]. Further data on patients with CCHS and Haddad syndrome in Korea should be gathered.…”
Section: Resultsmentioning
confidence: 99%
“…The combination is referred to as Haddad syndrome In Korea, Ahn et al [15] reported the first case of CCHS in 1993. Several additional cases have been reported to date [11,[16][17][18][19]. With early diagnosis and immediate intervention, the prognosis of CCHS patients has improved in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…It is a syndrome portraying inadequate respiratory responses to hypoxia and hypercapnia in the absence of a primary pulmonary, cardiac, metabolic, or neuromuscular disease or an identifiable brainstem lesion [6]. It was first described in 1970 by Mellins and colleagues, and since then its relation to PHOX2B gene mutations has been described together with its association with disorders of neural crest origin like Hirschsprung's disease [7][8][9][10]. The literary misnomer "Ondine's curse" has been used in prior literature and is based on a mythical story where a mortal knight Hans betrays Ondine the mermaid.…”
Section: Introductionmentioning
confidence: 99%